Health compromising components in French fries and fried chicken available in the markets of Dhaka city, Bangladesh - Sajia Islam; Shahrin Emdad Rayna; Fahmida Afroz Khan; K M Thouhidur Rahman; Md. Salman Mahbub Piyal; Barun Kanti Saha; Sharmin Jahan; Syed Shariful Islam; Md Khalequzzaman (CyTA - Journal of Food, 2023)
ABSTRACTFrench fries (FF) and fried chicken (FC) are known contributors to overweight and obesity among adolescents worldwide. Top selling five brands for both FF and FC were analyzed to determine their health compromising contents, which were sampled from the markets of Dhaka, Bangladesh. Sodium (Na) was determined by flame photometry, trans fatty acids (TFAs) by gas chromatography and heavy metals like arsenic (As), lead (Pb), cadmium and chromium by graphite furnace atomic absorption spectrophotometry. The median concentration of Na, TFA, As and Pb in FF was 0.45 gm/100 gm, 0.11 gm/100 gm, 0.93 mg/kg and 0.03 mg/kg, respectively. Similarly, in FC the median concentration of Na, TFA, As and Pb was 0.46 gm/100 gm, 0.13 gm/100 gm, 0.053 mg/kg and 0.06 mg/kg, respectively. The study findings suggests that consuming FF and FC impose a health risk among the exposed population.